Simulation of hysteresis loops for polycrystalline ferroelectrics by an extensive Landau-type model - Ying Long Wang (2018)
Landau-type phenomenological theory is extended to the polycrystalline ferroelectrics by defining a volume fraction of polarization to simulate polarization hysteresis loops. Using this simple model, polarization hysteresis loops of a model Pb(Zr0.52Ti0.48)O3ceramic at different fields or temperatures are simulated, it is found that our results are in very good agreement with the experimental data for the saturated as well as the unsaturated loops. Moreover, this model can accurately predict the coercive fields and remnant polarizations under arbitrary applied fields. © 2009 Elsevier B.V. All rights reserved.